Evaluation Tv- Image Quality for Different Cable Signal Transmission Resistance Based on Contrast Edge Algorithm (Journal of the College of Education for Women, 2019)
Some degree of noise is always present in any electronic device thattransmits or receives a signal . For televisions, this signal i has been to s thebroadcast data transmitted over cable-or received at the antenna; for digitalcameras, the signal is the light which hits the camera sensor. At any case, noiseis unavoidable. In this paper, an electronic noise has been generate onTV-satellite images by using variable resistors connected to the transmitting cable. The contrast of edges has been determined. This method has been applied bycapturing images from TV-satellite images (Al-arabiya channel) channel withdifferent resistors. The results show that when increasing resistance alwaysproduced higher noise for a television image .